Investigating Solar Wind‐Driven Electric Field Influence on Long‐Term Dynamics of Jovian Synchrotron Radiation. Issue 11 (28th November 2018) - Han, S.; Murakami, G.; Kita, H.; Tsuchiya, F.; Tao, C.; Misawa, H.; Yamazaki, A.; Nakamura, M.
Abstract: Since the first discovery of Jovian Synchrotron Radiation (JSR) from Jovian radiation belt in late 1950s, origin of its time variations has been one of the main subjects of the Jovian radiation belt study. JSR is reported to be strongly correlated with solar wind ram pressure with a possible time lag, which remains an unsolved issue. In our study, the influence of dawn‐to‐dusk electric field modulated with solar wind ram pressure on JSR variations is investigated. Alongside the original diffusion coefficient ( D LL (UV)), a new diffusion coefficient ( D LL (Elec)) which is dependent on solar wind conditions is applied to a one‐dimensional lossy radial diffusion model, and we reproduce long‐term variations of JSR between 1971 and early 2018. For the specific choice of D LL (UV) = 3.0 × 10 −10 L 3 [s −1 ], the correlation coefficient is found to be 0.6 between the simulated JSR and the ground observation data prior to 2005, and the intermittent observation after 2005 supports our simulation as well. We suggest that while D LL (UV) is the primary mode of diffusion that determines the steady profile of electron population and JSR, D LL (Elec) serves as a secondary mode, which controls long‐term variations of JSR. Key Points: Radial diffusion coefficient derived from dawn‐to‐dusk electric field fluctuations controlled by solar wind conditions is introduced The coefficient is comparable to dynamo electric field influence on Jupiter's upper atmosphere at the outer part of the radiation belt Our radial diffusion model provides the best reproduction of Jovian synchrotron radiation observed in the past